Deep Causes behind Brexit - Miklós Somai (Romanian Journal of European Affairs, 2021)
In an in/out referendum, held on 23 June 2016, the British electorate chose to leave the European Union. This paper uses the information and scientific outputs accumulated since the vote to explore and explain the deeper reasons behind Brexit. Key findings can be grouped in two categories. First of all, there are centuries long-standing endowments/factors – like history, geography, or differences in law or traditions, and, closely related to these, the legendary obsession with sovereignty and free trade – which have always been major drivers in influencing the British attitude towards Europe and have generally been reflected, in aspirations for a looser cooperation. Second, there are more recent factors – however, being around for the last 30-40 years – like changing balance of power (i.e., rising German influence) in the European institutions, or growing inequality in income, wealth, and opportunities, which may have been pushing some voters towards rejecting the status quo and embracing disruption as occasion emerged